If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -67 = 20 + 8x Reorder the terms: -67 + 5x = 20 + 8x Solving -67 + 5x = 20 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -67 + 5x + -8x = 20 + 8x + -8x Combine like terms: 5x + -8x = -3x -67 + -3x = 20 + 8x + -8x Combine like terms: 8x + -8x = 0 -67 + -3x = 20 + 0 -67 + -3x = 20 Add '67' to each side of the equation. -67 + 67 + -3x = 20 + 67 Combine like terms: -67 + 67 = 0 0 + -3x = 20 + 67 -3x = 20 + 67 Combine like terms: 20 + 67 = 87 -3x = 87 Divide each side by '-3'. x = -29 Simplifying x = -29
| 4lnx+7lnx=1 | | 25p^2-49=0 | | 15t-t= | | -4(-6-3x)=108 | | -204=6(-2+4x) | | (X+50)+(x+60)=90 | | 1.5x=-2y+11 | | (33/4-2/5)+5/8=x | | 0.06g= | | 2.9=7.7-0.6 | | 54=9(y+3) | | 9-5x=2x+4 | | 1+4n=17 | | 4n-12-18=-n | | 30=6xn | | 2y=11-1.5x | | 7x^6+52x^4+21x^2=0 | | 7.8x=3.4+x | | 9n+6=10 | | x+y+4z=19 | | 7(x+8)+5n=152 | | 7(f+9)=147 | | 7n+11=53 | | -5(5+4b)+3=-142 | | 5(8n-6)=-190 | | 3(5x-6)=102 | | -37y-7(40y+2)=4y+81 | | x-y-4z=19 | | 4n-7=29 | | 6(-2a+8)=96 | | 2x+(4x-40)=180 | | 3x+7=7x+4 |